2018
DOI: 10.1155/2018/9375067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insulin Injection Practice of Nurses Working in a Tertiary Healthcare Center of Nepal

Abstract: Introduction Sound knowledge and good practice on insulin injection technique are essential for nurses in order to administer insulin correctly and to educate patients or their relatives adequately. This study aimed to assess the insulin injection practice through the use of insulin pen among nurses working in a tertiary healthcare center of Nepal. Materials and Methods A cross-sectional descriptive study was conducted among 67 nurses working in one of the tertiary healthcare centers of Nepal. Demographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
7
9
1
Order By: Relevance
“…Our study revealed some deficiencies in insulin injection knowledge, attitudes, and practices, which was similar to the previous studies [11][12][13][14][15][16][17]. The study showed that only 64.81% of the nurses achieved a good or satisfactory knowledge score, which was in line with 66.2% of nurses at a tertiary care hospital in Hunan province, but lower than 83.5% of nurses at another tertiary care hospital in Guangdong province, suggesting that the insulin injection knowledge levels of nurses may differ across regions in China.…”
Section: Discussionsupporting
confidence: 90%
“…Our study revealed some deficiencies in insulin injection knowledge, attitudes, and practices, which was similar to the previous studies [11][12][13][14][15][16][17]. The study showed that only 64.81% of the nurses achieved a good or satisfactory knowledge score, which was in line with 66.2% of nurses at a tertiary care hospital in Hunan province, but lower than 83.5% of nurses at another tertiary care hospital in Guangdong province, suggesting that the insulin injection knowledge levels of nurses may differ across regions in China.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the nurses in this study were aware of the recommendations for insulin storage at room temperature. Contrasting findings were reported among nurses in Nepal [15] and Kenya [23].…”
Section: Discussioncontrasting
confidence: 76%
“…This could be attributed to the high turnover of nurses in The Gambia [16]. Similarly, Adhikari, et al, and Mohammed [15,17] reported that younger and less experienced nurses contributed to suboptimal patient care. Nurses are crucial frontline healthcare professionals and are responsible for proper insulin administration for diabetics admitted in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the evaluation of the insulin injection technique will depend on what is shown by the child and on other factors, such as the needles and syringes available and the professional's own control over the procedure. 34,35 In the overall content evaluation, measured in this study by CVR-S, both checklists obtained excellent evaluation, which affirms the relevance of the instruments for clinical practice. The answers to the open-ended question reinforce the importance of the syringe and the pen injection checklists in assessing the skills of children with T1D, benefiting the evidence-based practice.…”
Section: Discussionsupporting
confidence: 74%